2011
DOI: 10.1074/jbc.m110.200378
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide-stabilized Helical Hairpin Structure and Activity of a Novel Antifungal Peptide EcAMP1 from Seeds of Barnyard Grass (Echinochloa crus-galli)

Abstract: This study presents purification, activity characterization, and 1 H NMR study of the novel antifungal peptide EcAMP1 from kernels of barnyard grass Echinochloa crus-galli. The peptide adopts a disulfide-stabilized ␣-helical hairpin structure in aqueous solution and thus represents a novel fold among naturally occurring antimicrobial peptides. Micromolar concentrations of EcAMP1 were shown to inhibit growth of several fungal phytopathogens. Confocal microscopy revealed intensive EcAMP1 binding to the surface o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 53 publications
0
107
0
2
Order By: Relevance
“…The cysteine motif of these peptides may therefore be presented as: C1XXXC2-X(n)-C3XXXC4. The same cysteine pattern is shared by AMPs from two other cereals, maize (MBP-1) [15] and barnyard grass Echinochloa crus-galli (EcAMP1) [16], a dicotyledonous plant the Queensland nut Macadamia integrifolia (MiAMP2) [17], trypsin inhibitors from the ivy-leaved speedwell Veronica hederifolia (VhTI) [18] and buckwheat Fagopyrum esculentum (BWI-2b and BWI-2c) [19,20]. Moreover, we established the disulfide connectivity in Tk-AMP-X2, which was found to be identical to that in EcAMP1, VhTI, BWI-2b and BWI-2c.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cysteine motif of these peptides may therefore be presented as: C1XXXC2-X(n)-C3XXXC4. The same cysteine pattern is shared by AMPs from two other cereals, maize (MBP-1) [15] and barnyard grass Echinochloa crus-galli (EcAMP1) [16], a dicotyledonous plant the Queensland nut Macadamia integrifolia (MiAMP2) [17], trypsin inhibitors from the ivy-leaved speedwell Veronica hederifolia (VhTI) [18] and buckwheat Fagopyrum esculentum (BWI-2b and BWI-2c) [19,20]. Moreover, we established the disulfide connectivity in Tk-AMP-X2, which was found to be identical to that in EcAMP1, VhTI, BWI-2b and BWI-2c.…”
Section: Resultsmentioning
confidence: 99%
“…The peptide was cleaved at Met residues by cyanogen bromide, and the resulting mixture was analyzed by MS. Two fragments were identified with molecular masses of 1628 and 1831 Da. The latter corresponds to the middle part of the peptide (residues [9][10][11][12][13][14][15][16][17][18][19][20][21][22] containing the 'inner' Cys 9 -Cys 21 disulfide bond. The former corresponds to the two flanking parts (residues 1-8 and 23-28) held together by the 'outer' Cys 5 -Cys 25 disulfide bond.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that this inhibitor contains an unusual for inhibitors helix-turn-helix proteinase inhibitory motif. The subsequent analysis allowed us to reveal that VhTI is a member of wide group of plant peptides with antimicrobial and inhibitory activities found by other authors (Nolde et al, 2011;Park et al, 1997), first characterized by spatial structure. Their amino acid sequences can differ greatly from VhTI but also contain four cysteine residues in configuration nX-CXXXC-nX-CXXXC-nX.…”
Section: Trypsin Inhibitor From Seeds Of Veronica With An Unusual Helmentioning
confidence: 99%
“…In the case of distinctin, one intermolecular disulfide bond occurs between the two peptide chains, leading to an increase in peptide stability (due to the formation of a helix bundle structure in water) but not antimicrobial activity [43]. A recent study provides a novel example for helical AMPs with two disulfide bonds, which lock the two adjacent helices into a hairpin structure [44]. In addition, three disulfide bonds exist in the 10 saposin-like AMPs that form helix bundle structures [10].…”
Section: Disulfide Bridgesmentioning
confidence: 99%